2021
DOI: 10.1016/j.heliyon.2021.e08588
|View full text |Cite
|
Sign up to set email alerts
|

Land use effects on termite assemblages in Kenya

Abstract: Termites perform key ecological functions and they also cause crop damage. Land use change resulting from agricultural intensification can result in changes in termite species diversity and abundance. Termite species occurring in natural vegetation, maize monocrop and maize-beans intercrop macrohabitats were investigated in Embu and Machakos Counties, Kenya. Influence of soil properties and seasons was also evaluated. Across the two Counties, seven termite species were recorded with Machakos County having the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The results in Table 3 are in contrast to Bera et al [ 80 ], who reported that the height, masses, density, and regeneration rate of termite mounds increased with vegetation density in the order of grassland, dispersed, and dense vegetation. This discrepancy might be explained as certain land use practices affect the abundance and richness of termite communities, which could lead to the loss of functional groups in some cases [ 15 , 81 ]. According to Anyango et al [ 77 ], the abundance, occurrence, diversity, and foraging activities of termites also depend on soil depth, available feeding types, soil moisture, cropping season, and environmental location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results in Table 3 are in contrast to Bera et al [ 80 ], who reported that the height, masses, density, and regeneration rate of termite mounds increased with vegetation density in the order of grassland, dispersed, and dense vegetation. This discrepancy might be explained as certain land use practices affect the abundance and richness of termite communities, which could lead to the loss of functional groups in some cases [ 15 , 81 ]. According to Anyango et al [ 77 ], the abundance, occurrence, diversity, and foraging activities of termites also depend on soil depth, available feeding types, soil moisture, cropping season, and environmental location.…”
Section: Resultsmentioning
confidence: 99%
“…For Odontotermes and Macrotermes species, Kaiser et al [ 14 ] estimated about 216 and 32 t of soil material per ha per month on rehabilitative and barren land, respectively. This is because land use change results in termite species and diversity alterations [ 15 ]. Accordingly, when termites are involved in surface deposition and subsequent erosion from the mounds [ 16 ] with further downslope displacement, the soil ecosystem will be complex at the landscape scale, and termite pedoturbation will become more apparent.…”
Section: Introductionmentioning
confidence: 99%
“…Termites are destructive polyphagous insects that cause serious damage to crops. Termites seriously infest garden trees, timber, building materials, stored products, paper and clothing and cause enormous economic damage to them [8]. Termites infest the plant at different stages of growth [9].…”
Section: Introductionmentioning
confidence: 99%
“…Termites are highly destructive polyphagous pests that cause severe damage to crops [1]. Termites can seriously infect garden trees, timber, building materials, supplies, paper and clothing, causing enormous economic losses.…”
Section: Introductionmentioning
confidence: 99%
“…toxicity than synthetic pesticides (Figures[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It is well known that stored lipids are the most important and convenient stores of metabolic energy, meeting the long-term energy needs of insects under stress.…”
mentioning
confidence: 99%